The basal dunite of the Precambrian mafic-ultramafic Narankavaara intrusion : Petrogenetic considerations and implications to exploration - Jarvinen, Ville; Halkoaho, Tapio; Konnunaho, Jukka; Heinonen, Jussi S.; Ramo, O. Tapani (Mineralogy and Petrology, 2021)
Several mafic-ultramafic layered intrusions were emplaced in the Fennoscandian Shield during wide-spread mantle-sourced magmatism at 2.5-2.4 Ga. The Narankavaara intrusion (surface area 5 x 30 km(2)), northeastern Finland, contains a 1.5-2 km thick basal dunite (not dated), and a 1.5 km thick layered series (2436 +/- 5 Ma). A newly discovered marginal series between the basal dunite and the layered series indicates that the basal dunite is older, and highlights the need for further study on their relationship. Along its southern basement contact, the basal dunite contains a 200-300 m thick zone of olivine ortho- and mesocumulates, but the bulk of it is composed of olivine adcumulates and lesser olivine-orthopyroxene heteradcumulates. Based on whole-rock geochemistry, the basal dunite is divided into a low-Fe zone (average FeOt 10.2 wt% and Ni 2250 ppm) and a high-Fe zone (average FeOt 12.5 wt% and Ni 1700 ppm). Both zones have high MgO (32-47 wt%) and varying Cr (830-5160 ppm) and Al2O3/TiO2 (16-26). Textural and geochemical layering is similar along the 30 km strike of the basal dunite. A LREE-enriched high-MgO basaltic parental magma composition (13-18 wt% MgO) is inferred for the basal dunite from olivine-melt mixing trends in orthocumulates. The dunite exhibits at least two geochemical reversals as well as abundant low-porosity adcumulates, poikilitic chromite, and bimodal olivine, suggesting formation in a high-volume open magmatic system. Significant similarity in major and trace element compositions with the Narankavaara layered series and the Burakovsky intrusion and Vetreny belt extrusives in Russian Karelia suggests that the basal dunite belongs to the Fennoscandian 2.5-2.4 Ga mafic layered intrusions. An Archean komatiitic origin for the dunite body cannot be completely ruled out, however. Distinct Ni-depletion in olivine is found in the basal dunite from the low-Fe zone to the high-Fe zone (3200 versus 2200 ppm). This depletion does not correlate with Fo contents, which suggests that it is not ...